19x+12=18x+3

Simple and best practice solution for 19x+12=18x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 19x+12=18x+3 equation:


Simplifying
19x + 12 = 18x + 3

Reorder the terms:
12 + 19x = 18x + 3

Reorder the terms:
12 + 19x = 3 + 18x

Solving
12 + 19x = 3 + 18x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-18x' to each side of the equation.
12 + 19x + -18x = 3 + 18x + -18x

Combine like terms: 19x + -18x = 1x
12 + 1x = 3 + 18x + -18x

Combine like terms: 18x + -18x = 0
12 + 1x = 3 + 0
12 + 1x = 3

Add '-12' to each side of the equation.
12 + -12 + 1x = 3 + -12

Combine like terms: 12 + -12 = 0
0 + 1x = 3 + -12
1x = 3 + -12

Combine like terms: 3 + -12 = -9
1x = -9

Divide each side by '1'.
x = -9

Simplifying
x = -9

See similar equations:

| 4j-9j+j-4j-5= | | 2/3x^2-7=46 | | 0.2(18)+0.05x=0.1(24+x) | | -15d-12=-14d | | 3f-2+f-6= | | -5x+18+3(x-1)=8x-(7x-9)-6x+6 | | -4v-9=-6-v | | 12+50-14= | | -4(x+2)-44=8-36 | | 3x+13+3=2xsquared | | 10x=4(-2x+9) | | 6-5y=-4-6y | | 4x-2+3x= | | 46h=4h^3+5h^2 | | -7x-11y-5x+15y= | | -5x+18-3(x-1)=8x-(7x-9)+6x+6 | | V(x)=33x+162findx | | 12z+17=11z | | C=38.17+0.50 | | 2z^8/7z^7 | | v=144(3.14) | | 4(w-13)+17=19 | | -9x-5(3-4x)=6(x-4)-36 | | -7(x+4)= | | X=-(-10)/2(-5) | | 6h-h+2=17 | | 3x+7(x-9)=3(x-14) | | 6x+7=7x-1 | | Sin=-2 | | 14-w=17 | | cosz=-2 | | -1/2=3/5y-1/3 |

Equations solver categories